Attitudes of basic education teachers towards teaching social-emotional learning. (A field study in the first cycle schools in the city of Lattakia) - كحيلة, مرح; ميساء حمدان, (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research aimed to identify the attitudes of basic education teachers towards teaching the subject of social-emotional learning in schools in the city of Lattakia (the first cycle), and to reveal the differences between the opinions of teachers according to the variables (academic qualification, training courses). To achieve the goal of the research, the researcher used a questionnaire consisting of two sections: the first section, personal data, and the second section included (27) items divided into three axes, namely: (the cognitive dimension - the emotional dimension - the behavioral dimension). The research sample consisted of (182) teachers. In addition, a teacher of the teachers of the first cycle schools for the academic year 2023/2024, and to ensure its honesty and validity in terms of linguistic formulation and clarity, its comprehensiveness of the topics it included and its suitability to the goal for which it was developed. Therefore, it was presented to those with expertise and specialization in the College of Education, and its reliability was confirmed by applying it to a survey sample. It included (33) male and female teachers. The descriptive approach was used, and the research reached the following results: - The teachers’ attitudes towards teaching the subject of social-emotional learning are positive, as the overall average reached (3.09), which falls within the positive attitude category. - There are statistically significant differences between the average scores of basic education teachers on the attitudes questionnaire toward teaching the subject of social-emotional learning according to the academic qualification variable in favor of holders of an educational qualification diploma. - There are statistically significant differences between the average grades of basic education teachers regarding teaching the social-emotional learning subject according to the variable of following the training courses, in favor of those following the training courses. In light of the previous results, the research recommends the need to move towards preparing research and studies concerned with emotional education and the subject of social-emotional learning, working to study students’ attitudes towards this subject, and working to prepare specialized training programs to train teachers on the skills and activities of social-emotional learning, in addition to holding training courses for teachers. And educational supervisors in social-emotional learning.